Decreased mental health care utilization following a psychosocial intervention in caregivers of hematopoietic stem cell transplant patients - Rita Ouseph; Calvin Croy; Crystal Natvig; Teresa Simoneau; Mark L. Laudenslager (Mental Illness)
Caregivers are known to experience increased morbidity when compared to non-caregivers. Does an intervention targeting caregiver distress affect their health care utilization? One hundred forty-eight caregivers of allogeneic hematopoietic stem cell transplant patients were randomized to treatment as usual (TAU) or a psychoeducation, paced respiration, and relaxation (PEPRR) intervention. Assessments of caregivers’ service utilization were collected at baseline and 1, 3, and 6 months post-transplant. During the first 30 days after patient transplant, caregiver medical and mental health professional service use decreased while support group attendance peaked. Mixed model regressions showed a significant decrease in mental health service use by the PEPRR group (P=0.001). At six months caregivers in TAU had predicted marginal probabilities of mental health services utilization over 10 times as high as caregivers in PEPRR (18.1% vs 1.5%). Groups failed to differ in medical service (P=0.861) or support group (P=0.067) use. We can conclude that participation in PEPRR compared to TAU was associated with reduced mental health service utilization. Caregiver psychosocial support services are critical to improve caregiver outcomes.